Our share of night ebook A novel. - Enriquez, Mariana (2023)
“A masterpiece of supernatural horror.”— The Washington Post “An enchanting, shattering, once-in-a-lifetime reading experience.”— The New York Times (Editors’ Choice) ONE OF TIME AND THE ATLANTIC ’S TEN BEST NOVELS OF THE YEAR • ONE OF THE NEW YORK TIMES ’S TEN BEST HORROR BOOKS OF THE YEAR • LONGLISTED FOR THE DUBLIN LITERARY AWARD • GOOD MORNING AMERICA BUZZ PICK One of Reactor Magazine ’s Most Iconic Speculative Fiction Books of the 21st Century A woman’s mysterious death puts her husband and son on a collision course with her demonic family in the first novel to be translated into English by the International Booker Prize–shortlisted author of The Dangers of Smoking in Bed —“the most exciting discovery I’ve made in fiction for some time” (Kazuo Ishiguro). A BEST BOOK OF THE YEAR: The New York Times Book Review, NPR, The Washington Post, Esquire, Publishers Weekly, BookPage, Book Riot, PopSugar, The New York Public Library, Chicago Public Library, Polygon, Tordotcom, Lit Hub, Electric Lit, Commonweal, CrimeReads “A magnificent accomplishment.”—Alan Moore, author of Watchmen “A masterpiece of literary horror.”— Publishers Weekly, starred review “One of Latin America’s most exciting authors.”—Silvia Moreno-Garcia A young father and son set out on a road trip, devastated by the death of the wife and mother they both loved. United in grief, the pair travel to her ancestral home, where they must confront the terrifying legacy she has bequeathed: a family called the Order that commits unspeakable acts in search of immortality. For Gaspar, the son, this maniacal cult is his destiny. As the Order tries to pull him into their evil, he and his father take flight, attempting to outrun a powerful clan that will do anything to ensure its own survival. But how far will Gaspar’s father go to protect his child? And can anyone escape their fate? Moving back and forth in time, from London in the swinging 1960s to the brutal years of Argentina’s military dictatorship and its turbulent aftermath, Our Share of Night is a novel like no other: a family story, a ghost story, a story of the occult and the supernatural, a book about the complexities of love and longing with queer subplots and themes. This is the masterwork of one of Latin America’s most original novelists, “a mesmerizing writer,” says Dave Eggers, “who demands to be read.”